The Ambler Warning - Ludlum, Robert (St. Martin's Press, 2006)
On Parrish Island, a restricted island off the coast of Virginia,?is a little-known and never-visited psychiatric facility. There, far from prying eyes, the government stores former intelligence employees whose psychiatric states make them a danger to their own government, people whose ramblings might endanger ongoing operations or prove dangerously inconvenient. One of these employees, former Consular Operations agent Hal Ambler, is kept heavily medicated and closely watched. But there's one difference between Hal and the other patients - Hal isn't crazy. With the help of a sympathetic nurse, Hal manages to clear his mind of the drug-induced haze and then pulls off a daring escape. Now he's out to discover who stashed him here and why - but the world he returns to isn't the one he remembers. Friends and longtime associates don't remember him, there are no official records of Hal Ambler, and, when he first sees himself in the mirror, the face that looks back at him is not the one he knows as his own.